Managing Change in University Libraries in the 21st Century: An Australian Perspective. Issue 2 (2nd April 2020) - Gunapala, Matara; Montague, Alan; Reynolds, Sue; Vo-Tran, Huan
ABSTRACT: Managing change is documented as a critical issue for all organisations. Due to its complexity, a clear understanding of how university libraries can meet this challenge is yet to emerge. As libraries experience significant disruption as a result of technological development driving change, this qualitative research study advances a conceptual framework, based on relevant existing literature, for performance improvement. The research identified resources, relevance, stakeholders, strategy, government policy, and university infrastructure as contributing elements to effectively manage change in Australian public sector university libraries. This paper builds on this analysis to identify a shift in Australian university library management style and construct frameworks that may address challenges of change for these organisations.